Employment security and employee organizational citizenship behavior: does an 'iron rice bowl' make a difference?. Issue 13 (20th July 2019) - Liu, Xiaolang; Huang, Qihai; Wang, Hongli; Liu, Shanshi
Abstract: Empirical evidence linking employment security to organizational citizenship behavior (OCB) is equivocal. Limited research has considered the effect of employment status. Using data from 217 subordinate–supervisor dyads in a large state-owned enterprise in China as basis, our research found significant association between overall perceived employment security and employee OCB. However, this relationship may vary depending on employment status. Further analysis suggested a curvilinear relationship for permanent employees with an 'iron rice bowl' (lifetime employment) and a linear relationship for contractual employees without an 'iron rice bowl'. Our study contributes to a thorough understanding of the relationship between employment security and positive behaviors in terms of OCB by integrating the literature on social exchange, psychological contract, and proactive behavior.